Development of efficient absorbent for CO2 capture process based on (AMP + 1MPZ). (2022) - Dash, Sukanta Kumar; Parikh, Riya; Kaul, Daya
Abstract: Due to increasing global population and industrialization, global energy consumption has been increasing exponentially. At present, around 85% of energy is supplied by the burning of fossil fuels, which releases a large amount of CO2 to the atmosphere and this would continue for decades. An increase in CO2 in atmosphere is the major cause of global warming and climate change, leading to the demand for carbon neutrality and net zero emission scenarios. One of the effective ways to deal the situation is decarbonization through Carbon Capture Sequestration and Utilization (CCUS) through post-combustion CO2 capture (PCC) processes. But, these demand use of cheap and efficient CO2 capturing fluid for cost minimization. In this work, we have investigated an aqueous blended solvent containing 2-Amino-2-Methyl-1-Propanol (AMP) and 1-Methyl Piperazine (1MPZ). The blend has advantage of good thermodynamic equilibrium capacity contributed by AMP and good rate kinetics contributed by 1MPZ. Initially, the physico-chemical properties such as the density and viscosity of the solvents were investigated. The physical properties for the fresh as well as CO2 loaded solvents were investigated at wide range of temperature and composition. Thermodynamic equilibrium study of CO2 in the solvent having total amine concentration of 40 wt% was conducted at 40 °C. The equilibrium data was compared with the benchmarked solvent (30 wt% monoethanolamine (ME)) and found that the solvent used in this research is better than the benchmarked one. The other parameter for performance comparison is the cyclic CO2 loading capacity which is defined as the difference of CO2 loading between the absorption and regeneration. The CO2 cyclic capacity for a mixed amine blend of (20 wt% AMP + 20 wt% 1-MPZ) is 1.75 mol of CO2 /liter of solvent which is higher than that of 30 wt% MEA.